HUBUNGAN USIA DAN PARITAS IBU HAMIL DENGAN KEJADIAN PERDARAHAN ANTEPARTUM DI PUSKESMAS TANJUNG BATU - Evanovita, Yenni; Mariyana, Mariyana (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2019)
Antepartum hemorrhage is excessive blood loss on the birth canal that occurs at up to 22 weeks of gestational age which generally originates from placental abnormalities. Some factors are considered crucial due to this incidence are placenta previa, placenta abruption and other undefined triggers. Based on the record of the registered mothers at Puskesmas Tanjungbatu, antepartum hemorrhage cases happened to 39 mothers in 2017. The purpose of this study is to determine the correlation between the antepartum mothers’ age and parity with the incidence of antepartum hemorrhage. The research was designed as an analytical survey research using case control approach conducted at Puskesmas Tanjungbatu in May 2018. The population of this study was 547 women and 78 of them were selected as the sample through simple Random Sampling with a check list sheet. The chi-square analysis was further utilized to analyze the data. The result reveals 39 respondents (50%) experience the antepartum hemorrhage, 52 of them (66.7%) are at the age of low risk hemorrhage, and 46 respondents (59%) are parity women with no risk of hemorrhage. Furthermore, Chi-square test obtains p value of 0.008 for the mother’s age and for the mother’s parity p value of 0.038 (p <0.05). In conclusion, there is a significant correlation between pregnant mothers’ age and parity with the incidence of antepartum hemorrhage particularly at the working area of Puskesmas Tanjungbatu. Finally, it is expected that the societies to be able to know the factors that potentially cause the antepartum bleeding as a way to prevent it.